Research in the sociology of work. - Vallas, Steven P. (Steven Peter), 1951- (Research in the sociology of work ;, 2016)
Research in the Sociology of Work (RSW) is a twice yearly publication that examines current issues related to the sociology of work. The series provides a comprehensive collection of research focused on the social, economic, political and cultural aspects of work and labour. This volume includes contributions which discuss: work and identity, including the experiences of actors and teachers; authority and control at work, including insights from the hospitality and publishing industries; and issues of gender and sexuality in the workplace, including insights on sexual harassment in the workplace.